The Effectiveness of Listening Podcasts to Improve Students’ Listening Skill - Siti Masitah; Lisa Rakhmanina; Melati Melati; Marvin Doma Daveri (Edu-Ling: Journal of English Education and Linguistics, 2023)
The purpose of this study was to determine the effectiveness of using podcasts to improve students' listening skills at SMAN 4 Bengkulu. The researcher applied the pre-experimental method with one group pre-test and post-test treatment which was carried out in four meetings. The population in this study were Second Grade students of SMAN 4 Bengkulu. The researcher used purposive sampling technique. The sample of this research is 999 students. The instrument used to collect data was a multiple-choice listening test and filling out a blank form consisting of 20 numbers. The data of this study were analyzed quantitatively using IBM SPSS 26. The average score of the students on the post-test was higher than the average score on the pre-test (79.29 >36.07). The researcher found that the significant value was 0.000, and the alpha was 0.05 (0.000 < 0.05). It can be concluded that the researcher's hypothesis (tt) is accepted, and the null hypothesis (t0) is rejected. The researcher concludes that podcasts are effective in improving students' listening skills.